ANALISIS PARTISIPASI TERHADAP KESEJAHTERAAN ANGGOTA KOPERASI DI KPRI SERBA USAHA KARYAWAN UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Martini, Sri; Indyastuti, Nurhayati (Performance, 2010)
This research was carried out in Purwokerto, entitled:The Analyssis of Participation towards Cooperative Members’Walfare in kpri Serba Usaha Karyawan Universitas Jenderal Soedirman (KPRI KOSUKU) Purwokerto.The aims of research are to find out ang analyzehte effect of Cooperative Members Participation towards the welfare of Cooperative members themselves at KOSUKU Unsoed,besides that it aims to find out and analyze the paricipation variable that has the greatest effect towards the welfare of KOSUKU Cooperative members Unsoed. The proposed hypotheses research are:1. Participation has an effect towads cooperative members welfare2. The participation inusing available service has the greatest effet towardsmembers walfare The data werw collected through interview observation towards 100 members at KOSUKU Cooperative especially at cooperative store and inplaces wherethe nambers work. The data of research om respondents perceptions were analyzed using Path Analaysis,F-test and t-test. From research analysis it has got the result thst simulantneously Participation of Annual Members Meeting, Participation in Capital Investment and Participation in Using Available Service have sgnificant effect towards the welfare of KOSUKU Cooperative Members.It means the higher the participatoin of members the higher also the welfare of members. As the result af analysis it can also be found that out of three participation variables, Capital Investment Participation has the greatest effect on members welfare. As implication,it is suggested that KPRI KOSUKU organizer has to increase coperative capital through asking the cooperative members to increse their volunteer savings, to have a cooperation with banks to have loan to increse cooperative capital.Through sunh policy the cooperative can give greater credit low interst to its, members. Besides that Cooperative has to enlarge its store to be a Mini Market and having different service units for examples: motorcycle service repair shop electric payment service etc.All of these have the purpose to increse members' welfare.